The The Principals’ Strategy in Fostering the Performance of Teachers in the Driving School Program at SMA Negeri 15 Tanjung Jabung Barat - Retno Martanti; Muazza Muazza; Rd M Ali (Universitas Muhammadiyah Enrekang, 2023)
In order to achieve the objectives of this study, the research focus is on the description of strategies implemented by principals in an effort to improve teacher performance in the driving school program. This research was conducted in the environment of SMA Negeri 15 Tanjung Jabung Barat, Jambi Province. The research methodology applied was a descriptive qualitative approach with a phenomenological orientation. Data were obtained through observation, interview, and document analysis methods. The data analysis process includes data reduction, data display, and conclusion. The results showed that principals practiced various strategies to improve teacher performance, including discipline development and organizing internal training programs. The success of these strategies relies heavily on the commitment of the principal and teachers. As a leader, the principal is responsible for shifting the paradigm of Human Resources in his school to be willing to accept change, ensuring the successful implementation of the driving school program.